2019
DOI: 10.1534/g3.119.400430
|View full text |Cite
|
Sign up to set email alerts
|

Combining Transcriptomics and Proteomics Reveals Potential Post-transcriptional Control of Gene Expression After Light Exposure in Metarhizium acridum

Abstract: Light is an important stimulus for fungi as it regulates many diverse and important biological processes. Metarhizium acridum is an entomopathogenic fungus currently used for the biological control of insect pests. The success of this approach is heavily dependent on tolerance to environmental stresses. It was previously reported that light exposure increases tolerance to ultraviolet radiation in M. acridum . There is no information in the literature about how ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In these studies, conidia produced on scant media or under stressful conditions generally were more resistant to a UV irradiation than those produced on rich media or under normal culture conditions. In addition, fast‐growing M. acirdum hyphae became more tolerant to UVB after a short period of exposure to white or blue/UVA light because the light exposure induced the upregulation of a photolyase gene and transcriptional changes of many light‐responsive genes 62–64 . The UVB resistance of M. acridum and M. robertsii was enhanced in the conidia produced on a riboflavin‐inclusive medium relative to those produced on a riboflavin‐free medium 65 .…”
Section: Factors Affecting Fungal Uv Resistancementioning
confidence: 99%
“…In these studies, conidia produced on scant media or under stressful conditions generally were more resistant to a UV irradiation than those produced on rich media or under normal culture conditions. In addition, fast‐growing M. acirdum hyphae became more tolerant to UVB after a short period of exposure to white or blue/UVA light because the light exposure induced the upregulation of a photolyase gene and transcriptional changes of many light‐responsive genes 62–64 . The UVB resistance of M. acridum and M. robertsii was enhanced in the conidia produced on a riboflavin‐inclusive medium relative to those produced on a riboflavin‐free medium 65 .…”
Section: Factors Affecting Fungal Uv Resistancementioning
confidence: 99%
“…Despite this technical gap, our results contribute to the growing evidence obtained by combining transcriptomics and proteomics (or Ribo-Seq) approaches, showing that proteomes tend to be more stable, and/or to display a larger inertia to change, than transcriptomes. Such a trend has been communicated for yeasts species ( McManus et al, 2014 ), for the molecular responses of other fungi either to stressors or environmental cues ( Blevins et al, 2019; Brancini et al, 2019 ), as well as across primates ( Khan et al, 2013 ). In this regard, it has been shown that human tissues involved in similar broad functions display similar proteomes, even if their transcriptomes are divergent ( Wang D et al, 2019 ) and that this trend is conserved across evolutionary timescales for mammals ( Wang ZY et al, 2020) .…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of the UV stress response by a preliminary light exposure is a well known phenomenon, e.g. observed in Metarhizium acridum, and the respective molecular machinery of the signaling cascade leading to the upregulation of certain genes involved in the UV protection has been already described (Rangel et al 2015;Brancini et al 2016Brancini et al , 2018aBrancini et al , 2019Dias et al 2020). Experiments with testing different fungal species to UV stress may clarify this hypothesis.…”
Section: Effects Of Monochromatic Light On Soil Fungimentioning
confidence: 93%
“…Also, in a number of studies, photoinduced responses were measured after constant or protracted exposure of fungi to the light of various wavelengths. By contrast, much less data are available on the long lasting or delayed responses occurring after brief exposure, while such 'memory'-based effects in fungi has been known from classic studies (Zalokar 1955;Betina and Zajacova 1978;Schrott 1980) and confirmed in more recent experiments (Schmoll et al 2010;Brancini et al 2016Brancini et al , 2018aBrancini et al , 2019. And again, there is a gap in current knowledge regarding the species-related peculiarities of gross photoinduced reactions in such experimental conditions.…”
Section: ) Trichodermamentioning
confidence: 99%